Evaluation of the urban sponge stormwater regulation effectiveness based on SWMM: a case study of Wuhan, China - Lin, Yuru; Liang, Xiayuan; Xu, Jijun; Song, Zhihong; Lou, Yu; Yu, Yaoguo (Frontiers in Water, 2024)
BackgroundRapid population growth, urbanization, and high-intensity infrastructure development have challenged cities sustainable development. Surface water flooding occurs as a result of heavy rainfall which generates runoff that exceeds infiltration rates and local drainage capacity. In China, 70 cities have been chosen as pilot cities for sponge city construction building to address this challenge.MethodThis paper takes the South Trunk Canal in Qingshan Demonstration Area of Wuhan Sponge City as the study area. Based on construct a Stormwater Management Model (SWMM), simulate and analyze the runoff process and the drainage capacity of the pipe network before and after the construction of the sponge city in typical years with high, normal and low water flows and different return periods.ResultThe results show that the construction of sponge cities can significantly regulate the annual runoff in various typical target years and mitigate the overflow in 1- and 5- year return period. However, when faced with the short-duration storm events, the measures involved in urban sponge regulations are only effective for rainfall with 1-year return period. As the scale of the flood events increases, the effectiveness of urban sponge regulations becomes more limited.DiscussionTo address these issues, the National Water Network Project is proposed for the construction of water system connections. The aim of this project is to rectify the shortcomings of sponge cities while also making better use of water resources to improve overall resilience.